Qualitative Impact Assessment Protocol (QUIP) - Evaluation, Better
The QUIP sets out to generate differentiated evidence of impact based on narrative causal statements elicited directly from intended project beneficiaries without use of a control group. Evidence of attribution is sought through respondents’ own accounts of causal mechanisms link ing X to Y alongside Z rather than by relying on statistical inference based on variable exposure to X. This narrative data is intended to c omplement quantitative evidence on changes in X, Y and Z obtained thro ugh routine project monitoring.